2019
DOI: 10.5267/j.msl.2019.4.009
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of life and non-life insurances on ASEAN economic growth

Abstract: ASEAN is one of the regions with great potential of the world economic power. Countries included in the association of Southeast Asian countries are predicted to show strong economic growth. There are many factors for the development of the ASEAN region such as insurance industry. The Southeast Asian insurance industry, with a stable and long-term financial asset commitment, could play a bigger role in supporting the region's overall economic growth. This study aims at investigating the contribution of the ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
1
0
Order By: Relevance
“…In addition, the life insurance sector seems to attract little or no attention from the monetary authorities like the banking sector, creating a lapse in the development of the former. Thus, this result is consistent with the findings of Abdellahi and Fathi (2020) andMdanat et al (2019); but inconsistent with the findings of Oloyede et al (2023),Olaiya et al (2023), Shennaev (2020), and Safitri (2019.Lastly, this study showed that the real GDP growth rate tends to increase with an increase in life insurance density, but the outcome isnot remarkable enough. It revealed that Nigeria seems to have other factors responsible for the growth rate of the period, especially given the infinitesimal amount per person operating in this sector due possibly to the rate of poverty and low level of income of most people in the country.…”
supporting
confidence: 61%
“…In addition, the life insurance sector seems to attract little or no attention from the monetary authorities like the banking sector, creating a lapse in the development of the former. Thus, this result is consistent with the findings of Abdellahi and Fathi (2020) andMdanat et al (2019); but inconsistent with the findings of Oloyede et al (2023),Olaiya et al (2023), Shennaev (2020), and Safitri (2019.Lastly, this study showed that the real GDP growth rate tends to increase with an increase in life insurance density, but the outcome isnot remarkable enough. It revealed that Nigeria seems to have other factors responsible for the growth rate of the period, especially given the infinitesimal amount per person operating in this sector due possibly to the rate of poverty and low level of income of most people in the country.…”
supporting
confidence: 61%
“…It was found out that insurance sector premiums had no considerable influence on the GDP in Nigeria; however, the loans provided to private banks had significant effects on the economic growth in Nigeria. Safitri (2019) investigated the significance of life and non-life insurances on the economic development of the Association of Southeast Asian Nations between the years 2000-2005 with fixed effect model. It was found out in the study that the premiums of life and non-life insurance had affirmative and significant effects on economic growth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The insurance sector significantly mitigates unexpected occurrences and indemnifies insureds who suffer losses caused by the insured perils based on the insurance terms and conditions (Fadun & Shoyemi, 2018;Oladele & Uzoma, 2018). The insurance sector impacts a nation's economic activities directly and indirectly (Ayewumi & Awani, 2021;Safitri, 2019;Yeboah & Oppong, 2017). The insurance sector contributes to economic growth in developed and developing countries.…”
Section: Introductionmentioning
confidence: 99%